Na przełomie wieków - Szadek pod panowaniem Pruskim (1793-1806) - Włodarczyk, Zdzisław (Biuletyn Szadkowski, 2013)
In 1793, Szadek and the most of Greater Poland became a part of a new province named Southern Prussia by the conquerors. The town was subject to public administration (Kriegs- und Domanenkammer) in Piotrków, moved to Kalisz in 1798. At the same time, the centuries-old ties were severed. The town of Szadek and the activities of its inhabitants were similar to those in other urban centres of the region, except Kalisz and Piotrków. Agriculture was the basis of existence for a large part of the townspeople. It determined the wealth, or rather the poverty of the inhabitants. During the period, there was a population growth in the town from 671 to 1165 people - which means an increase of 74%. Most of the residents were soldiers deployed in the town with their families. A fire which took place on the 1911‘ October 1802 caused great devastation - 54 houses were burnt down. By the end of Prussian rule, the number of buildings was lower than in 1793. However, some new houses were built of durable materials. The reign of Prussians lasted for nearly 14 years. It ended after the defeat in the war with France in 1806. The inhabitants of Polish lands expected quick arrival of the victorious armies of Napoleon and declaration on the future of the lands reclaimed from Prussians.